Analisis Resiko Kegagalan Proses Kain jadi Polyester Menggunakan Metode FMEA pada PT XYZ Karawang - Rian Fernandi Fernandi (Ridwan Institute, 2022)
Proper quality control and clear stages and provide innovation in preventing and solving problems faced by the company. PT. XYZ Karawang is a textile industry company that produces polyester and cotton fabrics. In fact, this company still finds products with non-standard quality. From previous research data, the number of defects in polyester fabric tends to be quite high and does not comply with the standard, which exceeds the 2% set by the company. Meanwhile, the average product defect is 7,412 meters, about 5.4% of the total production each month is greater than cotton cloth. Therefore, the problem that arises is from polyester fabric which results in loss of cost of goods based on defects. FMEA is a technique used to identify the presence or potential of failures or problems in the design, process or structure of a sistem service before they occur, to prevent unwanted incidents and protect employees from occupational accidents and diseases by taking the necessary action. failures in the analyzed sistem are identified by FMEA, which enables the decision maker to take the necessary risk reduction actions. The purpose of this study is to analyze the failure modes that cause product defects using the FMEA method. The results of the research conducted based on the Risk Priority Number (RPN) there are 11 failure modes which are assumed to be the higher the failure mode RPN, the greater the risk for product failure and low quality. Of the 11 failure modes, the highest RPN value was 378, namely incomplete drug dissolution and the lowest was 27 with failure in the drug storage area. The factors that cause color spot defects on polyester fabrics are humans, raw materials, machines, methods used and the environment. In conclusion, the risk of failure in this study as a priority in the proposed improvement at the company PT. XYZ Karawang. Suggestions for improvement are given to the company as a whole to pay more attention to the factors causing the problem of fabric defects and as material for consideration in the company.